UNDERSTANDING MALAYSIANS BUMIPUTERA ENTREPRENEURS INVOLVEMENT IN HALAL BUSINESS: A CASE STUDY - Ismail, Risyawati Mohamed; Ismail, Noor Azizi (CENTRAL ASIA AND THE CAUCASUS, 2024)
This research investigated the involvement of Malaysia Bumiputera entrepreneurs in the halal business segment. Only 30% of halal entrepreneurs are Bumiputera, which raised concern among all stakeholders in the halal sector. The main objectives of this research was to determine what constitutes a successful Bumiputera halal entrepreneur. This research was done qualitatively, through case study on selected local halal entrepreneurs.The findings showed that, among others business opportunity, risk, value creation, business profit, and religiosity are among the motives driving the involvement in the halal business. This study also identified several characteristics that are common among successful Bumiputera entrepreneurs such as confidence, altruistic motivation, visionary, passionate, and pragmatic decision-makers. The findings of this research indicated a new contribution which was religiosity as part of the entrepreneurial mindset among halal business entrepreneurs in comparison with other entrepreneurs. In conclusion, local entrepreneurs’ involvement in halal business requires them to have several distinct characteristics which are similar to entrepreneurs from different sector, however when it comes to halal business the religiosity aspect of the industry became acutely important in propelling the drives within these business owners.